2014
DOI: 10.1007/s11010-014-2123-2
|View full text |Cite
|
Sign up to set email alerts
|

Long-term treatment with a beta-blocker timolol attenuates renal-damage in diabetic rats via enhancing kidney antioxidant-defense system

Abstract: The factors with increasing diabetes-prevalence lead to significant global increases in chronic kidney disease. Since hyperglycemia generates more ROS and attenuates cellular antioxidant-defense mechanisms, numerous studies demonstrated that hyperglycemia-induced oxidative stress played a major role in the extracellular matrix expansion in tissues. Although no direct relation between activation of beta-adrenergic (β-AR) system and kidney disease in diabetes and since β-blockers demonstrate marked beneficial ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…Streptozotocin is an antibiotic that is toxic to pancreatic islet β-cells and is commonly used to produce DM, and streptozotocin injection has been shown to produce oxidative stress, lipid peroxidation, and biochemical alterations such as reduced glutathione level and reduced glutathione and oxidised glutathione ratio and glutathione redox cycle enzymes (22, 32, 33, 34, 35). Therefore, researchers trying to find various extracts, drug-like molecules, antioxidant supplementations, vitamins, drug molecules to increase the enzyme activities which are responsible for improving GSH redox state, increasing reduced glutathione pool, and increase GSH/GSSG ratio and for cellular prevention against glucose toxicity, oxidative stress, enzyme activity normalizations in diabetic animal models (22, 35, 36, 37, 38, 39). In the present study, we have demonstrated that timolol treatment of STZ-induced diabetic rats had no noteworthy effect on high blood glucose level, while this treatment induced marked protection against hyperglycemia induced depressed activities of G6PD and 6PGDH in pancreatic tissue from STZ-induced diabetic rats.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Streptozotocin is an antibiotic that is toxic to pancreatic islet β-cells and is commonly used to produce DM, and streptozotocin injection has been shown to produce oxidative stress, lipid peroxidation, and biochemical alterations such as reduced glutathione level and reduced glutathione and oxidised glutathione ratio and glutathione redox cycle enzymes (22, 32, 33, 34, 35). Therefore, researchers trying to find various extracts, drug-like molecules, antioxidant supplementations, vitamins, drug molecules to increase the enzyme activities which are responsible for improving GSH redox state, increasing reduced glutathione pool, and increase GSH/GSSG ratio and for cellular prevention against glucose toxicity, oxidative stress, enzyme activity normalizations in diabetic animal models (22, 35, 36, 37, 38, 39). In the present study, we have demonstrated that timolol treatment of STZ-induced diabetic rats had no noteworthy effect on high blood glucose level, while this treatment induced marked protection against hyperglycemia induced depressed activities of G6PD and 6PGDH in pancreatic tissue from STZ-induced diabetic rats.…”
Section: Discussionmentioning
confidence: 99%
“…The experimental diabetic animal procedures, including timolol-treatment, were performed as described previously. Diabetes was induced by a single intraperitoneal injection of streptozotocin (STZ) (50 mg/kg body weight and dissolved in 0.1 mol/L citrate buffer, pH 4.5) in 3-month-old adult male Wistar rats (200–250 g body wt) (22). Rats with a blood glucose level >3 fold of controls were kept as diabetics (DM group) and tail vein fasting blood glucose levels were measured using a glucose analyser (Glucotrend, Roche).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Light microscopic evaluation was performed as described previously (24). Briefly, the excised heart samples were fixed in phosphate buffer/10% formaldehyde and dehydrated through a series of alcohol solutions.…”
Section: Histological Examinationmentioning
confidence: 99%